Grounding leadership ethics in African diaspora and election rights - Bongila, Jean-Pierre K., 1961- (Lexington Books, 2013)
The book exemplifies a comprehensive process of decision making from which various ethical leaders and particularly learners of leadership can find inspiration when facing such complex dilemmas as that of whether African expatriates ought to vote in their countries of origin. The examination of this issue from different ethical viewpoints and within the context of interdisciplinary perspective makes the methodology the book uses adaptable by anyone interested in the global consequences of globalization.